7 UMPSA subjects listed as world’s best in QS WUR by Subject 2024 - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 10 April 2024 - The seven subjects offered by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were listed among the world’s best in the recently announced QS World University Rankings by Subject 2024 rating.